CARBON TAX: ALTERNATIF KEBIJAKAN PENGURANGAN EXTERNAL DISECONOMIES EMISI KARBON - Rezky Nur Aisyah; Jamaluddin Majid; Suhartono Suhartono (ISAFIR: Islamic Accounting and Finance Review, 2020)
The purpose of this research is to determine the embodiment of carbon tax as an alternative policy to reduce external diseconomies of carbon emissions. This research is a qualitative study using comparative analysis (comparing policies) on the countries that applied carbon tax in the continental regions of Europe, America, and Asia, comprising the countries of Finland, Sweden, Norway, Denmark, France, Ireland, England, Mexico, British Columbia, and Japan. Research data obtained with a library study of various literature with major data sources is the state and trends of carbon pricing report by the worldbank. The research shows that carbon tax is a good policy for addressing external diseconomies of carbon emissions by giving a clear price signal, and potentially transforming households and industrial behavior for decision reduction in high-energy use emissions. In addition, the impact of carbon tax application shows sustainable development and the transformation of the green economy which can serve as low-carbon, resource efficiency and social inclusive, which can serve as a public policy that can improve capital allocation and environmental and social issues for future generations.